Methodology for Determining the Terms of Write-Off of Buses Operating in Tashkent City - Toxirjon-o‘g‘li, Karimov Islomjon; Jovliyev, Vasik Ulashevich; Inomjon-o‘g‘li, Otaqo‘ziyev Doniyor (European Journal of Life Safety and Stability (2660-9630), 2023)
This article, as buses age, the complexity of its current repair and downtime in maintenance and repair increase, the cost of spare parts and repairs increases, and the reliability of vehicle units and components decreases, which, in turn, leads to an increase in the number of sudden bus failures in during its operation on the route. Significant funds are spent every year to subsidize the expenses of passenger enterprises. The costs of ensuring the production activities of motor transport enterprises remain high, and the efficiency of the use of rolling stock is low, while the number of failures and malfunctions of buses on the line is increasing. In order for the standard service life related to this object to be used to determine the distribution parameters, we take into account that the standard service life is the calendar time during which the object must function properly.